2019
DOI: 10.3390/cells8020120
|View full text |Cite
|
Sign up to set email alerts
|

Host Vesicle Fusion Protein VAPB Contributes to the Nuclear Egress Stage of Herpes Simplex Virus Type-1 (HSV-1) Replication

Abstract: The primary envelopment/de-envelopment of Herpes viruses during nuclear exit is poorly understood. In Herpes simplex virus type-1 (HSV-1), proteins pUL31 and pUL34 are critical, while pUS3 and some others contribute; however, efficient membrane fusion may require additional host proteins. We postulated that vesicle fusion proteins present in the nuclear envelope might facilitate primary envelopment and/or de-envelopment fusion with the outer nuclear membrane. Indeed, a subpopulation of vesicle-associated membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 73 publications
(109 reference statements)
2
19
1
Order By: Relevance
“…Together, our results clearly point to a localization of a fraction of the cellular VAPB-pool at the INM. They are in line with a recent study that was published during the review process of this paper, suggesting a role of VAPB in nuclear egress of Herpes Simplex viral particles (30).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Together, our results clearly point to a localization of a fraction of the cellular VAPB-pool at the INM. They are in line with a recent study that was published during the review process of this paper, suggesting a role of VAPB in nuclear egress of Herpes Simplex viral particles (30).…”
Section: Resultssupporting
confidence: 92%
“…To our knowledge, a nuclear localization of VAPB itself has not been documented so far, except in a very recent publication (30). Using our rapamycin-dependent dimerization assay as well as immunoelectron microscopy, we now unequivocally show that VAPB can indeed reach the INM and can also be detected in close proximity to NPCs (Fig.…”
Section: Vapb At the Inmsupporting
confidence: 51%
“…In addition to the viral factors described above, host cell factors also contribute to vesicle formation at the INM during primary envelopment through as-yet undefined mechanisms. Vesicle-associated membrane protein-associated protein B (VAPB), which mediates cytoplasmic vesicle transport at the ER, facilitates HSV-1 nuclear egress [ 94 ]. Viral and cellular factors involved in HSV-1 primary envelopment are listed in Table 1 and Table 2 , respectively.…”
Section: Primary Envelopmentmentioning
confidence: 99%
“…Among these proteins are pUL31, which is a nuclear matrix-associated phosphoprotein; pUL34, a nuclear membrane-associated phosphoprotein; and Us3, a serine/threonine kinase that interacts with lamins A and C to disrupt the nuclear lamina in order to promote the envelopment of nascent viral capsids [ 192 , 195 , 196 ]. More recently, it has been reported that depletion of the host vesicle-associated membrane protein-associated protein B (VAPB) caused the accumulation of viral capsids in the nucleus, which supports its involvement in primary envelopment during nuclear egress [ 197 ]. Furthermore, the HSV-1 envelope protein US9 has been shown to associate with capsids in the cytoplasm, the endoplasmic reticulum and the Golgi apparatus, and to function in concert with gE/gI during anterograde transport within axons in neurons by promoting both the loading of capsids and glycoprotein-containing vesicles onto kinesin motors and microtubules [ 198 ].…”
Section: Exocytosis Vesicles Hijacked By Herpesvirusesmentioning
confidence: 99%